2017
DOI: 10.3389/fmicb.2017.02042
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Comparisons Reveal Microevolutionary Differences in Mycobacterium abscessus Subspecies

Abstract: Mycobacterium abscessus, a rapid-growing non-tuberculous mycobacterium, has been the cause of sporadic and outbreak infections world-wide. The subspecies in M. abscessus complex (M. abscessus, M. massiliense, and M. bolletii) are associated with different biologic and pathogenic characteristics and are known to be among the most frequently isolated opportunistic pathogens from clinical material. To date, the evolutionary forces that could have contributed to these biological and clinical differences are still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 75 publications
3
16
0
Order By: Relevance
“…We suspect that it is a result of the horizontal gene transfer between bacteria within the complex. This phenomenon was suggested as an important factor contributing to the evolution of M. abscessus 26,27 . M. abscessus is considered a pathogen with open, non-conservative pangenome, which means it should be monitored closely for the acquisition of pathogenic traits 28 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We suspect that it is a result of the horizontal gene transfer between bacteria within the complex. This phenomenon was suggested as an important factor contributing to the evolution of M. abscessus 26,27 . M. abscessus is considered a pathogen with open, non-conservative pangenome, which means it should be monitored closely for the acquisition of pathogenic traits 28 .…”
Section: Discussionmentioning
confidence: 97%
“…Tan et al found that recombination MABC more than mutations and natural selection. After a comparison of 243 genomes of M. abscessus, they found that the recombined sequences in the three subspecies have come from different intra-species and inter-species origins 27 . The observations of Tan et al reflected in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of M. abscessus , phylogenomic studies revealed the major role of recombination in causing lineage diversity [30,38,39]. Population structure and recombination analyses provided significant evidence of gene flow and admixture among three lineages ( M. abscessus , M. massiliense , and M. bolleti ), and a correlation with pathogenicity and macrolide resistance in cystic fibrosis patients was found [39].…”
Section: Availability Of Genome Sequences and Annotation Data: Applicmentioning
confidence: 99%
“…In recent years, MABS has been further characterized into three distinct subspecies; MABS subspecies abscessus , MABS subspecies bolletii and MABS subspecies massiliense ( Adekambi et al, 2017 ). They differ in terms of drug susceptibility, and may have differences related to transmissibility as well which will be discussed ( Tan et al, 2017 ). Genomic analysis of MABS reveals evidence of horizontal gene transfer ( Howard et al, 2002 ).…”
Section: Evolving Nomenclaturementioning
confidence: 99%